2018
DOI: 10.1016/j.burns.2017.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance training for rehabilitation after burn injury: A systematic literature review & meta-analysis

Abstract: Further research with robust methodology is recommended to assess the potential benefit suggested in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
8
0
11
Order By: Relevance
“…Additionally, PR programs using individually targeted exercises provide opportunities to improve PF, exercise tolerance, dyspnea symptoms, and skeletal muscles dysfunction in patients with chronic respiratory disorders (such as asthma and interstitial lung disease) [ 12 ]. Recent studies with thermal injury have shown that resistive exercises combined with aerobic exercises improve PF and muscle strength of the lower extremities [ 13 , 14 , 15 ]. Ozkal et al provides a strong suggestion for a personalized PR, including respiratory muscle strengthening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PR programs using individually targeted exercises provide opportunities to improve PF, exercise tolerance, dyspnea symptoms, and skeletal muscles dysfunction in patients with chronic respiratory disorders (such as asthma and interstitial lung disease) [ 12 ]. Recent studies with thermal injury have shown that resistive exercises combined with aerobic exercises improve PF and muscle strength of the lower extremities [ 13 , 14 , 15 ]. Ozkal et al provides a strong suggestion for a personalized PR, including respiratory muscle strengthening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical performance disorders can cause limitations of daily physical activities too. 11 Severe burns and the influences they have in the form of disability, defect, death and social and economic costs for the society are justified reasons for health care and society's paying particular attentions to this group of burn victims. 12 Nowadays, huge, predominantly patient-centered, progresses have been made in health care, treatment and prevention of burns and improvements of survival and quality of life.…”
mentioning
confidence: 99%
“…113 A recent meta-analysis on the effects of resistance training during burn rehabilitation found no significant overall improvement in lean muscle mass or muscle strength. 114 Although this result may seem surprising, it is rather a reflection of the limitations of current burn rehabilitation research; among the studies included in the meta-analysis, nine involved children and only two adult patients. Sample sizes were small, ranging from 20 to 40 patients, increasing heterogeneity.…”
Section: The Role Of Nutrition and Exercise In Mitigating Cachexia Anmentioning
confidence: 99%